Pemberdayaan Masyarakat Melalui Ekowisata pada Desa Pesisir di Kabupaten Bintan - Faizal Rianto; Billy Jenawi; Riau Sujarwani (Jurnal Pemberdayaan Masyarakat, 2021)
Ecotourism activities and the community-based ecotourism model are not new in Bintan District. Some coastal villages such as the Village of Kuala Sempang through Ballond Mangrove Tour and the Village of Pengudang through Pengudang Bintan Mangrove are even able to promote the mangrove forest ecotourism activities managed by the local communities. The success in promoting tourism potential through the concept of ecotourism in these villages certainly brings the hope of empowerment to the communities. Some studies even emphasize that tourism with the concept of ecotourism and community-based ecotourism models can contribute positively and can be used as a means or tool for community empowerment, especially for economically marginalized local communities. However, so far, studies on tourism in Bintan District are more focused on aspects of managing ecotourism activities, evaluating the development of ecotourism, and studying the potential of mangroves, while studies on community empowerment through ecotourism activities are needed to be encouraged to provide understanding based on empirical evidence of the impact and benefits of ecotourism activities for community empowerment, especially in coastal villages. Therefore, this study aims to describe how ecotourism activities empower the communities in coastal villages in Bintan District.